2012
DOI: 10.1093/cid/cis590
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Clinical Presentation, and In-Hospital Mortality of Severe Malaria in HIV-Coinfected Children and Adults in Mozambique

Abstract: Background. Severe falciparum malaria with human immunodeficiency virus (HIV) coinfection is common in settings with a high prevalence of both diseases, but there is little information on whether HIV affects the clinical presentation and outcome of severe malaria.Methods. HIV status was assessed prospectively in hospitalized parasitemic adults and children with severe malaria in Beira, Mozambique, as part of a clinical trial comparing parenteral artesunate versus quinine (ISRCTN50258054). Clinical signs, comor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
1
38
1
6
Order By: Relevance
“…In a previous study in Zambia, cases of severe malaria could not be confirmed in patients coinfected with HIV due to similarity of their clinical presentations with several opportunistic infections in AIDS patients (Chalwe et al, 2009). In another two prospective studies of severe malaria from Mozambique and Zambia both suggested that HIV-infected adults have a higher malaria case-fatality rate (Chalwe et al, 2009;Hendriksen et al, 2012). Hochman and Kim, 2009, claimed that HIV infection tends to increase episodes of symptomatic malaria and risk of severe or complicated malaria including death in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in Zambia, cases of severe malaria could not be confirmed in patients coinfected with HIV due to similarity of their clinical presentations with several opportunistic infections in AIDS patients (Chalwe et al, 2009). In another two prospective studies of severe malaria from Mozambique and Zambia both suggested that HIV-infected adults have a higher malaria case-fatality rate (Chalwe et al, 2009;Hendriksen et al, 2012). Hochman and Kim, 2009, claimed that HIV infection tends to increase episodes of symptomatic malaria and risk of severe or complicated malaria including death in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Severe malaria in HIV co‐infected patients presents with higher parasite burden, more complications and more frequent comorbidity and carries a higher case‐fatality rate (Hendriksen et al . ). Caution is needed when attributing complications to P. falciparum infection, as HIV immunosuppression also increases susceptibility to many of the opportunistic infections that cause clinical illnesses that might be mistakenly attributed to malaria in populations with a high prevalence of incidental parasitaemia.…”
Section: Section 3: Clinical Features Of Severe Falciparum Malaria Inmentioning
confidence: 97%
“…; Hendriksen et al . ). Obtaining a parasitological diagnosis does not resolve the diagnostic problem, especially in high transmission areas, where asymptomatic parasitaemia is common and may be incidental in any severe illnesses (Gwer et al .…”
Section: Section 9: Clinical and Laboratory Diagnosis Of Severe Malariamentioning
confidence: 97%
See 1 more Smart Citation
“…While there is increased mortality in adults co-infected with malaria and HIV in areas with unstable malaria transmission, this phenomenon has not been established in areas with stable malaria transmission [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%